Relearn how to make and keep friendships the way children do - Abd Razak, Dzulkifli (2004)
DURING this Hari Raya celebration, at least one girl will be very un happy. Nur Liyana has just lost a dear friend — Huang Na (picture). They were the best of pals. They attended school together and "chatted nonstop while walking home" almost everyday. Under the watchful eye of Nur's grandmother, they shared, played and laughed together. Then a month ago, eightyearold Huang Na vanished. Nur waited patiently for her friend to return. Eventually, it became clear she was gone forever. Huang Na was found murdered, her body stuffed in a box in dense undergrowth in Singapore. A spirit of honest friendship that resonates in the nation as we celebrate Hari Raya and Deepavali.